Urinary Tract Infections, Associated Risk Factors and Antibacterial Susceptibility Profile Among Pregnant Women in Central Ethiopia - Ketema Bizuwork Gebremedhin; Haile Alemayehu; Girmay Medhin; Wondwossen Amogne; Katarina Slaba; Girma Belay; Shubhada Bopegamage; Tadesse Eguale (Infectious Microbes & Diseases, 2025)
Abstract. In addition to anemia, urinary tract infection (UTI) is a common pregnancy issue that affects the health of the mother and her fetus. The aim of this study was to estimate the prevalence of UTIs and determine risk factors, the bacterial profile and antibacterial susceptibility in pregnant women in central Ethiopia. Serially diluted urine samples were inoculated onto plate count agar for CFU determination. Standard conventional microbiological testing techniques were used to identify bacterial uropathogens at the species level. The Kirby-Bauer disc diffusion method was used to evaluate antibacterial susceptibility. A binary logistic regression model was employed to investigate factors linked to the prevalence of UTIs. Out of the 873 pregnant women recruited, 180 (20.6%) had culture-confirmed UTIs, the majority of whom (n = 165, 91.7%) were asymptomatic. A body mass index ≤24.9 (adjusted OR = 0.61, 95% CI = 0.39–0.98, P < 0.05) was found to be protective against UTIs. The most often identified bacterial uropathogen was Escherichia coli (n = 85, 45%), followed by Klebsiella pneumoniae (n = 23, 12.0%), Staphylococcus aureus (n = 17, 9.0%) and Enterococcus faecalis (n = 14, 7%). A large proportion of the E. coli isolates were resistant to amoxicillin (n = 74, 87.1%). More than half of the S. aureus isolates (n = 10, 58.8%) were methicillin-resistant. The high prevalence of UTIs and antibacterial resistance and the detection of rarely encountered UTI-causing bacterial uropathogens are concerning factors. These findings highlight the need for routine UTI screening and drug susceptibility testing before treatment to minimize complications during the perinatal period.